AUDITING CLASS REFERENCE: LITERATURE REVIEW OF THE STANDARD ANALYTICAL PROCEDURES FOR AUDITING - Hendi; Harsono, Budi; Averina; Alvina; Tedia (Global Financial Accounting Journal, 2025)
Purpose – This research aims to summarize the work of existing scientific articles and review literature on the standard analytical procedures for auditing, to serve as additional guiding literature that can be used as a reference for learning and research ideas related to analytical procedures in auditing classes or courses. Research Method – Through qualitative analysis using a systematic literature study with a meta-analysis of 10 accredited international articles, this research summarizes and identifies research results and lessons learned, implications, and future research directions from the existing literature on standard analytical procedures for auditing. This research is expected to provide a foundation for further learning and research on aspects of analytical procedures in the audit process. Findings – The results of this study indicate that research directions that can be considered on the topic of standard analytical procedures for audits are the integration of the latest technology, automation of procedures, comparative application analysis, and ways to improve auditor competence in an audit environment that is constantly required to evolve with the times and the industry. This study confirms that the topic of standard analytical procedures for auditing has a lot of room and potential to be explored and evaluated in the future. Implication – This study has important implications for academics, universities, educators, and students as users of teaching and learning materials about the field of auditing, as well as developers of research and policy in the audit sector.